Decarcerating disability: deinstitutionalization and prison abolition - Ben-Moshe, Liat (University of Minnesota Press, 2020)
"Politics of (En)closure: Deinstitutionalization, Disability, and Prison Abolition argues that a complex understanding of disability is fundamental to an understanding of decarceration. Many argue that the rise of deinstitutionalization led directly to the rise of imprisonment. Liat Ben-Moshe complicates this narrative by looking closely at how people of color and disabled people are pathologized as well as how profit plays a roll in caring for "disposable" populations in nursing homes, rehab facilities, prisons, etc. Ben-Moshe puts forth a theory of carceral abolition as a way to understand the failed utopian dream of deinstitutionalization and how to move forward"--